Production of matrices with molybdenum as an alternative to matrices with cobalt in diamond cutting tools - Çelik, Ertuğrul; Islak, Serkan; Ilkiliç, Cumali (Institute of Metals Technology, 2014)
This study is about the production of new matrices that are an alternative to cobalt matrices in diamond cutting tools. Thus, Fe, Cu, Al2O3 and Mo were used as the matrix components. The mass fractions of 1 %, 2 % and 3 % Mo were added to the matrix. The production of matrices was performed in a fully automatic hot-pressing machine under 35 MPa of pressure, at a sintering temperature of 850 °C, with a dwell period 4 min. The microstructures and phase compositions of the matrices were established with a scanning electron microscope (SEM-EDS) and an X-ray diffractometer (XRD). The hardness and bending strength of the segments were determined. The transverse rupture strength (TRS) of the segments was determined using the three-point bending test. The results revealed that Mo increased the bending strength and hardness of the segments.
Keywords: Diamond cutting tool; Mechanical properties; Microstructure; Molybdenum